2002
DOI: 10.1002/bies.10036
|View full text |Cite
|
Sign up to set email alerts
|

Derangement of growth and differentiation control in oncogenesis

Abstract: Human neoplasms develop following the progressive accumulation of genetic and epigenetic alterations to oncogenes and tumor suppressor genes. These alterations confer a growth advantage to the cancer cell, leading to its clonal proliferation, invasion into surrounding tissues, and spread to distant organs. Genes that are altered in neoplasia affect three major biologic pathways that normally regulate cell growth and tissue homeostasis: the cell cycle, apoptosis, and differentiation. While each of these pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Tumor transformation involves the progressive accumulation of genetic and epigenetic alterations to tumor suppressor genes and oncogenes (Ross et al, 2000;Corn and El-Deiry, 2002). The genes that are altered during tumorigenesis mainly affect cell growth, apoptosis, and the differentiation of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor transformation involves the progressive accumulation of genetic and epigenetic alterations to tumor suppressor genes and oncogenes (Ross et al, 2000;Corn and El-Deiry, 2002). The genes that are altered during tumorigenesis mainly affect cell growth, apoptosis, and the differentiation of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Meticulously regulated differentiation, proliferation and apoptosis play fundamental roles in the development of multicellular organisms and the maintenance of tissue homeostasis (Abrams 2002, Corn & El-Deiry 2002. We previously found that ACTH is able to induce differentiation and apoptosis, but it inhibits proliferation of rat fetal adrenocortical cells in primary cultures (Arola et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Liver stem cells proliferate, then differentiate, in response to trauma, stress, or during normal development [22]. HepG2 cells recapitulate this balance, as they are capable of both proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 96%